Dividend Investing Using “Big Safe Dividends” to Build Equity Portfolios in Brazil - Matheus da Silva Viana, Dener; Vinicio de Almeida Lima, Lauro; Silva Martins, Orleans (Review of Business Management, 2024)
Purpose – This study investigates the efficiency of Big Safe Dividends (BSD) as an investment strategy for building successful portfolios in the Brazilian stock market. Theoretical framework – Using Carlson’s (2010) model, stocks with high dividend potential are identified and portfolios of 10, 15, 20, and more stocks are constructed. These portfolios are analyzed over the period from 2010 to 2023. Design/methodology/approach – The performance of the BSD portfolios is compared to the main Brazilian stock market indices (IBOV, IDIV, IBrX, and IGC). The alpha generation of these portfolios is assessed using OLS regression models based on multi-factor asset pricing models, incorporating Fama and French’s (1992, 1993) five risk factors, Carhart’s (1997) momentum factor, and Amihud’s (2002) liquidity factor. Findings – The results show that BSD portfolios consistently outperform the four benchmark indices over the period analyzed. The study confirms that the use of BSD is effective in forming stock portfolios that generate positive and significant alphas. Practical & social implications of research – The primary contribution of this study is the evidence supporting BSD as a valid indicator of a dividend factor, showing that the criteria for selecting companies that pay big and safe dividends successfully capture dividend risk, which is priced in the Brazilian market. Originality/value – This finding is unique in the context of investment strategies related to dividend investing in Brazil, offering novel insights for investors focusing on dividend-based portfolios. Keywords – dividend yield; investment strategy; factor investing.